Penerapan Platform Pembelajaran Nearpod untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VIII SMP Negeri 3 Sungguminasa - Nurrahmadani A.; Ramlawati Ramlawati; Sitti Rahma Yunus (Universitas Negeri Makassar, 2026)
This research aims to determine 1) the level of learning outcomes of class VIII students at SMPN 3 Sungguminasa by implementing the nearpod learning platform on the subject matter of light and optical instruments, 2) improving the learning outcomes of class VIII students at SMPN 3 Sungguminasa by applying the nearpod learning platform to the subject matter light and optical devices, 3) whether or not there is a significant increase in the learning outcomes of class VIII students at SMPN 3 Sungguminasa after implementing the nearpod learning platform on the subject matter of light and optical devices, 4) whether or not there are similarities in the learning outcomes of class VIII students at SMPN 3 Sungguminasa after implementing the nearpod learning platform on the subject matter of light and optical devices. This type of research is pre experiment and One Group Pretest-Posttest Design research design with 2 experimental classes. The population in this study was all 11 class VIII students, while the sample was chosen using purposive sampling so that the sample in this study was class VIII A and class VIII B students with a total sample of 61 students. The research instrument is in the form of learning outcome test questions. Data analysis was carried out using descriptive and inferential analysis. The results of the analysis concluded that the application of the nearpod learning platform could improve the learning outcomes of class VIII students at SMPN 3 Sungguminasa and there were similarities in the learning outcomes of students in classes VIII A and VIII B at SMPN 3 Sungguminasa after implementing the nearpod learning platform.